Shuri. 1, The search for Black Panther - Okorafor, Nnedi (Marvel Worldwide, Inc., a subsidiary of Marvel Entertainment, LLC, 2019)
"The Black Panther has disappeared, lost on a mission in space. And in his absence, everyone's looking at the next in line for the throne. But Shuri is happiest in a lab, surrounded by gadgets of her own creation. She'd rather be testing gauntlets than throwing them. But a nation without a leader is a vulnerable one - and Shuri may have to choose between Wakanda's welfare and her own"--Provided by publisher.